(untitled) - Bornstein, David (New York, 2010)
In development circles, there is now widespread consensus that social entrepreneurs represent a far better mechanism to respond to needs than we have ever had before--a decentralized and emergent force that remains our best hope for solutions that can keep pace with our problems and create a more peaceful world.
Keywords: Social entrepreneurship,Social entrepreneurship,Social change,Thay đổi xã hội,Cộng đồng doanh nhân